Tanggung Jawab Perusahaan Perencana Keuangan Penyedia Program Investasi yang Merugikan Konsumen Dihubungkan dengan Teori Kepastian Hukum - Vivi Nur Arzy; Yeti Sumiyati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
The principle of responsibility as one of the principles of GCG is reflected in the Company Law that every company may not carry out activities that are contrary to the law. This responsibility principle is also applied to companies engaged in the capital market. Financial planning companies are companies whose activities are connected to the capital market and can support the capital market. However, the regulations regarding financial planners have not been specifically regulated in statutory provisions. The existence of a legal vacuum regarding financial planners is used as an opening to commit violations by one of the financial planning companies so that it results in losses for consumers. This study used a normative juridical approach using a descriptive analytical research specification. The data collection technique used is through literature study using laws, books, journals and the internet related to the topic of the problem which will later be used as a reference for solving problems as part of data analysis. The analytical method used legal construction through the analogy method which is used to find specific provisions that become general provisions so that they can be applied to financial planning companies. The conclusions obtained from this research are: First, the regulation regarding financial planners in Indonesian laws and regulations has not been specifically and specifically regulated so that the existence of financial planners has not received legal certainty. Second, responsibility for financial planning companies providing investment programs that harm consumers can be subject to administrative, civil and criminal sanctions.